Motivation and Attitude of Domestic Tourists to Travel in the New Normal Era - Ni Ketut Seminari; I Gusti Agung Ketut Sri Ardani (International Journal of Management Research and Economics, 2025)
Bali is still a favorite destination for both foreign and domestic tourists. For the people of Indonesia, Bali is the choice as a very attractive tourist destination. The uniqueness of Bali is a motivation for domestic tourists to always come to visit. Since the covid 19 pandemic, tourist arrivals have decreased drastically. Although it is slow because it is still struggling with the Covid-19 pandemic, signs of Bali tourism rising are starting to appear. Tourists began to determine their attitude to come to Bali during the holiday season. Tourist visits have started to increase since October 2020. This study aims to look at the influence of motivation and attitudes of domestic tourists deciding to travel to Bali in the new normal era. The number of respondents in the study were 109 respondents. Analyzed using moderated regression analysis (MRA). The results of this study indicate that motivation has a positive and significant effect on travel decisions, attitude has a positive and significant effect on travel decisions, new normal has a positive and significant effect on travel decisions. New normal significantly weakens the effect of motivation on travel decisions. New normal is not proven to moderate the effect of attitude on travel decisions.